Off label use of direct oral anticoagulants for left ventricular thrombus. Is it appropriate? - Degheim, George (Am J Cardiovasc Dis, 2017)
A 57 year old gentleman with a history of non-ischemic cardiomyopathy and paroxysmal atrial fibrillation presented with worsening lower extremity edema and dyspnea on exertion. He had been compliant with his medications including rivaroxaban (Xarelto) for atrial fibrillation that he takes with the evening meal daily. His echocardiogram showed an ejection fraction of 10-15% and a new left ventricle (LV) apical thrombus. During his hospital stay, he developed right sided weakness. Magnetic Resonance Imaging showed a subacute infarct involving the left parietal lobe. The decision was made to discontinue rivaroxaban and initiate heparin infusion instead. Meanwhile, the patient’s neurological symptoms were closely monitored. The patient was then transitioned to warfarin. He was eventually transferred to the rehabilitation floor with minimal residual neurologic weakness. Left ventricular thrombus is an important complication in the setting of systolic dysfunction. The combination of blood stasis, endothelial injury and hypercoagulability, is a prerequisite for in-vivo thrombus formation. The slow onset of action and reversal, need for frequent monitoring, narrow therapeutic range, dietary restrictions, and multiple drug interactions limit the use of vitamin K antagonists. Direct-acting oral anticoagulants (DOACs) do not have these limitations and may also reduce the risk of hemorrhagic stroke. Our patient developed an LV thrombus while on uninterrupted DOAC therapy.